Landscape Design: Analyzing Site Conditions - Gail Hansen; Erin Alvarez (EDIS)
ENH1165, a 4-page illustrated fact sheet by Gail Hansen and Erin Alvarez, takes homeowners through the process of developing an inventory and analysis of their yards to determine action items toward achieving the desired results in their landscape design. Includes additional sources of information. Published by the UF Department of Environmental Horticulture, June 2010.